Dl-3-N-Butylphthalide Presents Anti-Cancer Activity in Lung Cancer by Targeting PD-1/PD-L1 Signaling - Jiang Q (Dove Medical Press, 2021)
Qian Jiang,1– 3 Nan Zhang,2 Xin Li,2 Wei Hou,4 Xiao-Qing Zhao,5 Lei Liu1,2 1Department of Head and Neck Oncology, Department of Radiation Oncology, Cancer Center, West China Hospital of Sichuan University, Chengdu, 610041, Sichuan, People’s Republic of China; 2State Key Laboratory of Biotherapy, West China Hospital of Sichuan University, Chengdu, 610041, Sichuan, People’s Republic of China; 3Department of Oncology, Affiliated Hospital of North Sichuan Medical College, Nan Chong, 637000, Sichuan, People’s Republic of China; 4Department of Pathology, Affiliated Hospital of North Sichuan Medical College, Nan Chong, 637000, Sichuan, People’s Republic of China; 5Department of Oncology, The Second Affiliated Hospital of North Sichuan Medical College, Nan Chong, 637000, Sichuan, People’s Republic of ChinaCorrespondence: Lei Liu Email liuleihx@gmail.comIntroduction: Lung cancer serves as one of the most malignant cancer types. Immunotherapy targeting PD-1/PD-L1 axis is a promising strategy for cancer treatment. Dl-3-N-butylphthalide (NBP), a small molecule compound extracted from the seeds of Apium graveolens, possesses a large range of biological effects and demonstrates anti-cancer activities. However, the role of NBP in the modulation of lung cancer remains obscure.Methods: In this study, we aimed to explore the effect of NBP on PD-L1 signaling and the progression of lung cancer.Results: Significantly, the treatment of NBP repressed the proliferation of lung cancer cells in vitro. Tumorigenicity analysis in nude mice showed that the tumor volume and tumor weight were attenuated by the treatment of NBP in the mice. Meanwhile, the levels of Ki-67 and PD-L1 were reduced by the treatment of NBP in the tumor tissues of the mice. NBP suppressed IFN-γ-induced PD-L1 enhancement in lung cancer cells. The treatment of NBP inhibited PD-L1 expression in lung cancer cells co-cultured with unstimulated PBMCs or activated T cell. NBP inhibited PD-1 expression in activated T cells co-cultured with lung cancer cells. Conditioned medium from activated T cells increased PD-L1 expression, and NBP reversed this effect. Co-culture with A549 and H1975 cells reduced T cell proliferation and activity, while the treatment of NBP reversed the reduction. Consistently, the treatment of NBP caused notably decreased apoptosis of co-cultured T cells. Mechanically, KAT7 was able to bind to PD-L1 promoter and epigenetically induce PD-L1 expression by promoting the enrichment of histone H3 lysine 14 acetylation (H3K14ac) and RNA polymerase II on PD-L1 promoter.Discussion: Thus, we concluded that NBP repressed PD-L1 expression by targeting KAT7 and attenuated PD-1/PD-L1 axis to relieve lung cancer progression. NBP may be applied as the potential therapeutic strategy in immunotherapy of lung cancer.Keywords: lung cancer, Dl-3-N-butylphthalide, KAT7, PD-1/PD-L1 axis, immunotherapy